The “save the earth!” narrative creates a narrative trap for climate advocates - Laird, Frank N. (Frontiers in Climate, 2022)
The phrase “Save the Earth!” triggers the dominant narrative among climate advocates, one of environmentalists battling polluters to save Mother Earth from being despoiled. In this narrative the moral boundaries are clear and the stakes are apocalyptic, leaving no room for doubt or compromise. Nonetheless, the narrative has failed over decades to resolve policy deadlocks over climate change, to rebuff attacks from opponents of those policies, and to create a winning political coalition that could overcome the deeply institutionalized barriers to transforming large social and technological systems. Climate advocates need a new narrative, one that will continue to decarbonize the economy but must also emphasize adapting to climate change that is already in the pipeline and ensure that efforts to decarbonize do not harm the most vulnerable parts of the population nor frustrate the aspirations of people around the world who seek better lives for themselves. The burgeoning field of just energy transitions encompasses these concerns, but it too needs a new story, one that avoids the narrative traps that have hampered climate policy more generally. The burgeoning field of just energy transitions encompasses these concerns, but it too needs a new story, one that avoids the narrative traps that have hampered climate policy more generally. The burgeoning field of just energy transitions encompasses these concerns, but it too needs a new story, one that avoids the narrative traps that have hampered climate policy more generally.